Exploratory Subject Searching in Library Catalogs: Reclaiming the Vision. - Bauder, Julia; Lange, Emma (Information Technology & Libraries, 2015)
Librarians have had innovative ideas for ways to use subject and classification data to provide an improved online search experience for decades, yet after thirty--‐plus years of improvements in our online catalogs, users continue to struggle with narrowing down their subject searches to provide manageable lists containing only relevant results. This article reports on one attempt to rectify that situation by radically reenvisioning the library catalog interface, enabling users to interact with and explore their search results in a profoundly different way. This new interface gives users the option of viewing a graphical overview of their results, grouped by discipline and subject. Results are depicted as a two--‐level treemap, which gives users a visual representation of the disciplinary perspectives (as represented by the main classes of the Library of congress Classification) and topics (as represented by elements of the Library of Congress Subject Headings) included in the results.